Structural relaxation in terms of TNM and AGS models - Svoboda, Roman; Honcová, Pavla; Málek, Jiří (University of Pardubice, 2009)
In this article the structural relaxation of non-crystalline materials was studied. The materials researched in this work were the amorphous selenium, Ge2Se98, As2Se98, and poly(vinyl acetate). Two types of relaxation – volumetric and enthalpic – were studied by using mercury dilatometry and differential scanning calorimetry. The relaxation of the materials studied was described on the basis of the Tool-Narayanaswamy-Moynihan (TNM) and Adam-Gibbs-Scherer (AGS) models. The main objective of this work was to describe and compare the volume and enthalpy relaxation of glassy Se, Ge2Se98, As2Se98 and PVAc.